2015
DOI: 10.1142/s1793292015300029
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Prefabricated Tunnel Junction-Based Molecular Spintronics Devices

Abstract: Molecule-based devices may govern the advancement of the next generation's logic and memory devices. Molecules have the potential to be unmatched device elements as chemists can mass produce an endless variety of molecules with novel optical, magnetic and charge transport characteristics. However, the biggest challenge is to connect two metal leads to a target molecule (s) and develop a robust and versatile device fabrication technology that can be adopted for commercial scale mass production. This paper discu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 124 publications
0
16
0
Order By: Relevance
“…(MSDs) have attracted worldwide attention due to their potential to revolutionize logic and memory devices [1,2]. A typical MSD is comprised of two ferromagnetic (FM) electrodes-coupled by molecular channels [3,4]. Molecular channels with a net spin state are the basis of a large number of intriguing studies [5], which were either observed experimentally [6,7] or were calculated theoretically [2].…”
Section: Introduction: Molecular Spintronics Devicesmentioning
confidence: 99%
“…(MSDs) have attracted worldwide attention due to their potential to revolutionize logic and memory devices [1,2]. A typical MSD is comprised of two ferromagnetic (FM) electrodes-coupled by molecular channels [3,4]. Molecular channels with a net spin state are the basis of a large number of intriguing studies [5], which were either observed experimentally [6,7] or were calculated theoretically [2].…”
Section: Introduction: Molecular Spintronics Devicesmentioning
confidence: 99%
“…However, these two approaches have been extremely difficult to mass produce robust molecular spintronics devices [5]. With conventional approaches it is also almost impossible to conduct extensive magnetic studies to explore the true effect of molecules on the magnetic properties of the molecular spintronics devices [6]. To date most of the experimental studies have only focused on the transport studies-no direct magnetic measurements were performed [3,4,7].…”
mentioning
confidence: 99%
“…To date most of the experimental studies have only focused on the transport studies-no direct magnetic measurements were performed [3,4,7]. To overcome the limitations of the conventional molecular spintronics devices magnetic tunnel junctions (MTJ), produced by sandwiching an insulator between two ferromagnetic electrodes, were utilized as the test bed [5,6,8]. Under this approach an MTJ with the exposed side edges can enables the covalent bonding of desired molecular channels onto the two ferromagnetic electrodes along the junction perimeter [5].…”
mentioning
confidence: 99%
“…3,4 Molecular channels with a net spin state are the basis of a large number of intriguing studies, 5 which were either observed experimentally 6,7 or were calculated theoretically. 2 Porphyrins, 8 single molecular magnets 2 and magnetic molecular clusters 9 possess a net spin state and can be synthetically tailored to be employed in a MSD.…”
Section: Introductionmentioning
confidence: 99%